Society for Immunotherapy of Cancer consensus statement on immunotherapy for the treatment of renal cell carcinoma. Issue 1 (December 2016) - Rini, Brian; McDermott, David; Hammers, Hans; Bro, William; Bukowski, Ronald; Faba, Bernard; Faba, Jo; Figlin, Robert; Hutson, Thomas; Jonasch, Eric; Joseph, Richard; Leibovich, Bradley; et al.
Abstract Immunotherapy has produced durable clinical benefit in patients with metastatic renal cell cancer (RCC). In the past, patients treated with interferon-alpha (IFN) and interleukin-2 (IL-2) have achieved complete responses, many of which have lasted for multiple decades. More recently, a large number of new agents have been approved for RCC, several of which attack tumor angiogenesis by inhibiting vascular endothelial growth factors (VEGF) and VEGF receptors (VEGFR), as well as tumor metabolism, inhibiting the mammalian target of rapamycin (mTOR). Additionally, a new class of immunotherapy agents, immune checkpoint inhibitors, is emerging and will play a significant role in the treatment of patients with RCC. Therefore, the Society for Immunotherapy of Cancer (SITC) convened a Task Force, which met to consider the current role of approved immunotherapy agents in RCC, to provide guidance to practicing clinicians by developing consensus recommendations and to set the stage for future immunotherapeutic developments in RCC.